Sports-related sudden death in the general population - Marijon, E.; Tafflet, M.; Celermajer, D. S.; Dumas, F.; Perier, M.-C.; Mustafic, H.; Toussaint, J.-F.; Desnos, M.; Rieu, M.; Benameur, M.; Le Heuzey, J.-Y.; Empana, J.-P.; et al. (Circulation, 2011)
Background: Although such data are available for young competitive athletes, the prevalence, characteristics, and outcome of sports-related sudden death have not been assessed previously in the general population.